Kajian Pola Tumpangsari Jahe dengan beberapa jenis sayuran terhadap hasil Jahe = Study of Intercropping between Ginger and Vegetables, Its Effect on the Yield of Ginger - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The purpose of this experiment was to determine the appropriate vegetables that was intercropped with ginger at different cropping patterns. The experiment was conducted at the Agricultural Training Research and Development (ATRD) Station, Gadjah Mada University at Kalitirto, Berbah, Sleman, Yogyakarta Province, during the period of October 2001 up to February 2002. A factorial experiment of 3 x 5 factors was employed, where the treatments were arranged in Split Plot Design with 3 replicates. The main plots which were arranged in Latin Square Design were consisted of intercropping between ginger and vegetables, namely: (1) ginger with stringbean, (2) ginger with corn, and (3) ginger with shallot. As the sub plots were proportions between ginger and vegetables, consisted of 5 level namely: (100%:'0%), (75% : 25%), (50% : 50%), (25% : 75%), and (0% : 100%) respectively. The theoritical framework adopted in this experiment was replacement series theory. Results of the experiment showed that: (1) Intercropping between ginger and vegetables at different patterns gave a significant effect on the yield of ginger